Evaluation of textile industry wastes: Cellulose recovery from cotton/ polyester blend shearing waste - Elkamel, Hude; Tasar, Seyda; Duranay, Neslihan; Yilgin, Melek (Pergamon-Elsevier Science Ltd, 2025)
In this study, the recovery efficiency of cellulose from shearing waste (SW), one of the textile industry wastes consisting of cotton/polyester blends, was investigated. Transforming textile industry wastes into high-valueadded secondary products is important in terms of environmental sustainability and waste management. The main purpose of the study presented in this context is to reveal the economic and ecological potential of these wastes and to contribute to the development of a sustainable waste management model. Our study was carried out with a three-stage methodology. First, shearing wastes used as raw materials were supplied and characterized. In the second stage, cellulose was recovered using various chemical pretreatments (acid hydrolysis, alkaline hydrolysis, and organosolvent treatment), and the recovery efficiency was calculated. In the third stage, the recovered cellulose fractions were subjected to a detailed characterization process. It was determined that approximately 97% of the cellulose from the wastes could be recovered cumulatively as a result of the process carried out with the combination of the mentioned chemical pretreatments. The recovered cellulose showed varying crystallinity index (65-75%) and thermal stability depending on the process parameters. As a result, it was concluded that textile wastes have the potential to be converted into high-value products. It was revealed that it supports the protection of national natural resources and zero waste policies. In addition, the study tried to present evaluations regarding the complexity and applicability of the methodology and suggestions for improving textile waste management strategies. This research includes data and evaluations that can be important in terms of waste management and environmental policies in the textile industry and provide an important reference point. Future studies should focus on optimizing the solvent recovery system and increasing industrial-scale applicability.
Keywords: Shearing waste; Cellulose recovery; Chemical pretreatment; Cellulose characterization; Zero-waste policy; Textile industry